Evaluation of design quality and its impact on execution in private housing projects in Kuwait - Bumejdad, Sadeq Yahya; Elnakhely, Mohamed Ezzat (Journal of engineering sciences and information technology, 2024)
Various technical challenges have emerged during the construction phase of private residential buildings. Some of these issues have been attributed to low design quality. This study focused on evaluating the quality of private residential design, the factors affecting design quality, the impact of these factors on project execution, and strategies to enhance quality during the planning and design phases. The study utilized previous research, expert interviews, and an analytical descriptive approach The study used quantitative and qualitative data, where case studies of private housing projects in Kuwait were analyzed, Quantitative data were also collected by using a questionnaire as a tool to obtain responses from the sample of project parties. The results of the study showed the low level of design and its documents in private housing projects in Kuwait. It contributed to delaying the execution of projects by an average percentage of 51.8% of the total factors, while it contributed to increasing the cost of projects by an average percentage of 39.3% of the total factors. Design deficiencies were linked to multiple factors attributed to the project consultant: inadequate technical efficiency, poor coordination, lack of project review, insufficient project details, and reuse of designs from similar prior projects. Contributing factors on the client’s part: an inability to clearly define project requirements due to limited owners’ experience, consultant selection based on cost rather than qualifications, and late design changes during the execution phase. Other less impactful factors: weak communication among project stakeholders, insufficient time allocation for the design phase, and the absence of a unified local design code. A comprehensive framework of recommendations was developed with key suggestions: the activation of continuous monitoring and assessment of consulting offices, establishment of comprehensive approach to design quality evaluation, requiring design teams to obtain practice licenses from the Kuwait Society of Engineers based on skill assessments, promoting awareness among clients regarding consultant selection criteria.
Keywords: Design quality; execution quality; design documentation; private housing; project designers; drawings